Average Bandwidth Allocation Model of WFQ - Tomáš Balogh; Martin Medvecký (Modelling and Simulation in Engineering)
We present a new iterative method for the calculation of average bandwidth assignment to traffic flows using a WFQ scheduler in IP based NGN networks. The bandwidth assignment calculation is based on the link speed, assigned weights, arrival rate, and average packet length or input rate of the traffic flows. We prove the model outcome with examples and simulation results using NS2 simulator.